Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Harga Saham Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI - Sesfia Fahrauri Fairurachma (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This research is motivated by factors that influence stock prices through the variables Profitability, Liquidity and Leverage which have different results. This research aims to determine the effect of profitability, liquidity, and leverage on stock prices of the food and beverage sub-sector listed on the Indonesia Stock Exchange. The dependent variable in this research is stock price measured by annual closing price, while the independent variables are profitability as measured by Earning Per Share (EPS), liquidity as measured by the Current Ratio (CR), and leverage as measured by the Debt to Equity Ratio. (DER). The research method used descriptive and verification methods. The data collection technique used documentation techniques with secondary data types originating from the official website of the Indonesia Stock Exchange in the form of financial reports and company annual reports. The population in this research amounted to 12 companies for 10 years of observation from 2011-2020. Based on the determination of the sample using the saturated sampling method, the sample used is 12 companies and the observation data is 120 data. Hypothesis testing in this research was carried out using panel data regression. The results of the regression significance test show that the regression model means that it can be used to draw conclusions. The results of hypothesis analyst show that profitability has a positive effect on stock prices, while liquidity and leverage have no effect on stock prices.